Identifying and overcoming barriers to participation of minority populations in clinical trials: Lessons learned from the VanDAAM study. (7th July 2022) - Fink, Angelina K. C.; DeRenzis, Amanda C.; Awasthi, Shivanshu; Jahan, Nawreen; Johnstone, Peter A. S.; Pow‐Sang, Julio; Torres‐Roca, Javier; Grass, Daniel; Fernandez, Daniel; Naghavi, Arash; Tan, Susan; Manley, Brandon; et al.
Abstract: Participation in cancer research trials by minority populations is imperative in reducing disparities in clinical outcomes. Even with increased awareness of the importance of minority patient inclusion in clinical research to improve cancer care and survival, significant barriers persist in accruing and retaining minority patients into clinical trials. This study sought to identify and address barriers to minority accrual to a minimal risk clinical research study in real‐time. Abstract : Participation in cancer research trials by minority populations is imperative in reducing disparities in clinical outcomes. Even with increased awareness of the importance of minority patient inclusion in clinical research to improve cancer care and survival, significant barriers persist in accruing and retaining minority patients into clinical trials. This study sought to identify and address barriers to minority accrual to a minimal risk clinical research study in real time.